Genetic evidence that PpsR from Rhodobacter sphaeroides 2.4.1 functions as a repressor of puc and bchF expression. - Gomelsky, M (1995)
The ppsR gene (R. J. Penfold and J. M. Pemberton, J. Bacteriol. 176:2869-2876, 1994) from Rhodobacter sphaeroides 2.4.1 functions as a transcriptional repressor of puc and bchF expression. The carboxy terminus of PpsR, containing the putative DNA-binding domain, by itself possesses repressor activity. Intact palindromes having the motif TGT-N12-ACA are required for PpsR activity.